1995
DOI: 10.1152/ajpendo.1995.269.1.e18
|View full text |Cite
|
Sign up to set email alerts
|

A limitation in the use of mass isotopomer distributions to measure gluconeogenesis in fasting humans

Abstract: The use of distributions of mass isotopomers in glucose from [U-13C]glycerol to estimate fractional rates of gluconeogenesis was examined. [U-13C]glycerol was infused into normal subjects who ingested acetaminophen and fasted for 60 h. Isotopomer distributions were measured by mass spectrometry in blood glucose and in glucuronic acid from urinary acetaminophen glucuronide. The distributions are incompatible with glucose production solely via gluconeogenesis from a single pool of triose phosphates. Rather, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 15 publications
3
58
1
Order By: Relevance
“…In accordance with the absence of a single precursor pool, when [U-13 C 3 ]glycerol was infused for 5 h into healthy subjects fasted for 60 h the contribution of GNG to glucose production was estimated to be only 60 % (Landau et al 1995b), and only 78 % when infused with [2-13 C]glycerol for 4 h (Hellerstein et al 1997), rather than > 90 % expected with glycogen depletion. The greater percentage contribution with [2-13 C]glycerol when compared with [U-13 C 3 ]glycerol can be explained by the need to infuse more [2-13 C]glycerol, resulting in a smaller concentration gradient along the liver lobule.…”
Section: Mass-isotopomer-distribution Analysismentioning
confidence: 79%
See 2 more Smart Citations
“…In accordance with the absence of a single precursor pool, when [U-13 C 3 ]glycerol was infused for 5 h into healthy subjects fasted for 60 h the contribution of GNG to glucose production was estimated to be only 60 % (Landau et al 1995b), and only 78 % when infused with [2-13 C]glycerol for 4 h (Hellerstein et al 1997), rather than > 90 % expected with glycogen depletion. The greater percentage contribution with [2-13 C]glycerol when compared with [U-13 C 3 ]glycerol can be explained by the need to infuse more [2-13 C]glycerol, resulting in a smaller concentration gradient along the liver lobule.…”
Section: Mass-isotopomer-distribution Analysismentioning
confidence: 79%
“…in the example described earlier the triose phosphate pool is uniform in containing 10 % of the molecules with three 13 C. However, uptake of glycerol is almost complete in its single passage through the liver. Hepatocytes closer to the portal-vein area of the liver lobule are therefore exposed to much higher concentrations of the glycerol than hepatocytes in the hepatic-vein area, relative to other GNG substrates (Landau et al 1995b;Previs et al 1995). Thus the decrease in lactate concentration along the lobule is not as great.…”
Section: Mass-isotopomer-distribution Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The potential advantage of this approach is that it would circumvent the problems previously discussed that result in the underestimation of gluconeogenesis by other tracer techniques. However, when Landau et al (1995a) infused [U-13 C]glycerol into normal subjects who had fasted for 60 h and calculated the proportion of glucose derived from gluconeogenesis using MIDA, they found that only about half the glucose was seemingly derived via this pathway, as opposed to the approximately 100 % that would be expected. This underestimation apparently resulted because the precursor (i.e.…”
Section: Gluconeogenesismentioning
confidence: 99%
“…Evidence has been provided (Neese et al, 1995;Peroni et al, 1995Peroni et al, , 1996 for the in vitro and in vivo validity of this method for calculating gluconeogenesis when using [2-13 C]glycerol infusion to label hepatic TP. However, other authors (Landau et al, 1995b; Glucose from gluconeogenesis will be labeled but glucose from glycogenolysis will also be labeled since cycling between glucose-6 phosphate and fructose-6 phosphate takes place at a much higher rate than glucose production from glucose-6 phosphate through glucose-6 phosphatase activity. Therefore, the amount of deuterium bound to carbon 6 relative to that bound to carbon 2 provides a measure of the fraction of glucose formed via gluconeogenesis (Landau et al, 1995c (Lee et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%